THE ECOLOGICAL SITUATION OF THE ARARAT BASIN AND RATIONAL USAGE OF ITS SOIL RESOURCES (Proceedings of the YSU C: Geological and Geographical Sciences, 2006)
The modem ways of exploitation of soil and water resources of the Ararat basin are a good basis to suppose that in the near future new soil layers will be thrown out of the agricultural usage because of their second salting and swamping. A new type of scientifically grounded drainage-meliorative activities which will basically change the ecological state of the basin is suggested.
Keywords: Ararat basin; new soil layers; drainage-meliorative activities